Stigma »Kopftuch«: Zur rassistischen Produktion von Andersheit - Kreutzer, Florian (transcript, 2015)
The stereotypical stigmatization of the headscarf is a practice of anti-muslim racism. On the basis of qualitative interview data, Florian Kreutzer reveals daily practices of racist discrimination, of `doing race' and racial othering - and likewise the practices and possibilities of undoing race, of crossing out, undermining, overcoming and undoing the racist production of alterity. The stories about veiled women make it clear that in the ways that they combine family and work, that they cannot be essentially distinguished from other women. The racist production of alterity becomes recognizable as a social practice and structural dimension of modern societies.